Pengaruh Penerapan Problem-Based Learning menggunakan Media Mentimeter terhadap Hasil Belajar Peserta Didik Kelas X Mata Pelajaran Informatika di SMKN 2 Malang - Inneke Yola Ferdiana Hadi; Satrio Hadi Wijoyo; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The research was motivated by the lack of understanding of the materials by the teacher to students which affected student learning outcomes. Thus, this study aims to determine whether there is an influence from the application of the problem-based learning method using the media Mentimeter on the learning outcomes of class X ULW students in understanding informatics subjects at SMKN 2 Malang. In this study used a weak experimental approach (weak experimental design). The research design used in this research is The Static Group Pretest-Posttest Design. This study used a quantitative approach with research subjects of class X ULW 3 SMKN 2 Malang as the experimental class and class X ULW 2 SMKN 2 Malang as the control class. There are differences in the learning outcomes of the experimental class and the control class of class X students of SMK Negeri 2 Malang in informatics subjects. The Independent Sample T-test shows that it is known that the calculated t value is -3.549 is 0.001 so that on this basis it can be concluded that Ho is rejected or concluded that there is a significant difference in the post-test filling by the experimental group and the control group. The average post-test using Mentimeter which is 75 which is greater than using PowerPoint media which is only 69, so there are differences in student learning outcomes using Mentimeter and student learning outcomes using Powerpoint. The learning outcomes of Informatics subjects by students at SMKN 2 Malang using the Mentimeter media are better than using Powerpoint media because students experience increased learning outcomes when learning using Mentimeter.